Non-medical use of opioid analgesics in contemporary Brazil: Findings from the 2015 Brazilian National Household Survey on Substance Use. Issue 2 (1st February 2020) - Krawczyk, Noa; Silva, Pedro Luis do Nascimento; De Boni, Raquel B.; Mota, Jurema; Vascncellos, Mauricio; Bertoni, Neilane; Coutinho, Carolina; Bastos, Francisco I.
ABSTRACT: Prior studies on substance use in Brazil have not focused on opioid misuse, previously thought to be nearly non-existent. This paper presents new findings on heroin and non-medical use of opioid analgesics. Data come from the 2015 Brazilian Household Survey on Substance Use (BHSU-3), a nationally representative survey estimating epidemiological parameters related to substance use by residents across Brazil. BHSU-3 used stratified multi-stage probability sampling across multiple geographic domains of interest, resulting in 16, 273 interviews with household residents. Lifetime heroin use among Brazilians was 0.3 (95% C.I:0.2–0.4). Lifetime, past-year, and past-month non-medical use of opioid analgesics were respectively 2.9 (95%C.I.:2.3–3.4), 1.4 (95%C.I.:1.1–1.7) and 0.6 (95%C.I.:0.4–0.8). Past-year prevalence of non-medical opioid analgesics use was lower among males [Prevalence Ratio (PR): 0.54 (95% C.I.:0.36–0.78)], those aged 12–24 [0.56 (95% C.I.:0.34–0.92)], persons with monthly family incomes between R$1, 501–3, 000 [0.59 (95% C.I.:0.38–0.92)] or greater than R$3, 000 [0.64 (95% C.I.:0.42–0.98)], and persons who were unemployed [0.65 (95% C.I.:0.46–0.92)]. Non-medical use of opioids in Brazil may be more prevalent than previously recognised. Proper measurement and evaluation of opioid misuse across Brazil and other Latin American countries is critical to understand and prevent opioid-related harms.